2021
DOI: 10.1093/gbe/evab022
|View full text |Cite|
|
Sign up to set email alerts
|

A Naturally Heteroplasmic Clam Provides Clues about the Effects of Genetic Bottleneck on Paternal mtDNA

Abstract: Mitochondrial DNA (mtDNA) is present in multiple copies within an organism. Since these copies are not identical, a single individual carries a heterogeneous population of mtDNAs, a condition known as heteroplasmy. Several factors play a role in the dynamics of the within-organism mtDNA population: among them genetic bottlenecks, selection, and strictly maternal inheritance are known to shape the levels of heteroplasmy across mtDNAs. In Metazoa, the only evolutionarily stable exception to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…It is still largely unclear whether this phenotype might be adaptive for enhanced male functions, and we cannot exclude that the remodelled mitochondrial bioenergetics in DUI sperm might be maladaptive, resulting from perpetuate inefficient selection on DUI M-mtDNA. On that end, a recent comparison between M-type alleles found in sperm or in male soma of the DUI R. philippinarum revealed tissue-specific difference in allele frequency distribution, potentially as a result of different selective forces acting on male gonads and adductors (strong versus more relaxed selection) [50]. Overall, our results reinforce what was detected in previous studies [36][37][38], namely that the control of mitochondrial respiration at the terminus of the respiratory chain might be under strong selective pressures to potentially ensure appropriate metabolic regulation of M-type mitochondria in DUI species.…”
Section: (B) Gametes In Species With Doubly Uniparental Inheritance Of Mitochondriamentioning
confidence: 99%
“…It is still largely unclear whether this phenotype might be adaptive for enhanced male functions, and we cannot exclude that the remodelled mitochondrial bioenergetics in DUI sperm might be maladaptive, resulting from perpetuate inefficient selection on DUI M-mtDNA. On that end, a recent comparison between M-type alleles found in sperm or in male soma of the DUI R. philippinarum revealed tissue-specific difference in allele frequency distribution, potentially as a result of different selective forces acting on male gonads and adductors (strong versus more relaxed selection) [50]. Overall, our results reinforce what was detected in previous studies [36][37][38], namely that the control of mitochondrial respiration at the terminus of the respiratory chain might be under strong selective pressures to potentially ensure appropriate metabolic regulation of M-type mitochondria in DUI species.…”
Section: (B) Gametes In Species With Doubly Uniparental Inheritance Of Mitochondriamentioning
confidence: 99%
“…The presence of M-type mtRNA in somatic tissues seems to vary across DUI species, for example 60% male somatic samples in U. peninsularis and 89.5% male somatic samples in V. ellipsiformis presented somatic transcription of M-type mt genes ( Breton et al, 2017 ). In R. philippinarum , previous work reported variable number of M-type DNA and RNA in somatic tissues, depending on the individual ( Ghiselli et al, 2011 ; Iannello et al, 2021 ; Milani et al, 2014 ). In this work, we found that M-type is barely transcribed in the somatic tissues of most males.…”
Section: Discussionmentioning
confidence: 97%
“…One possibility could be the narrower germline bottleneck of M-type mtDNA. Past studies indicated that the F-type mtDNA copy number in eggs is on average 10 times higher than the copy number of M-type mtDNA in sperm ( Ghiselli et al, 2011 ), and that the narrower genetic bottleneck in M-type mtDNA could lead to the segregation of mtDNA variants in different tissues, causing remarkable within-individual variation and therefore also higher variability between samples ( Iannello et al, 2021 ). Alternatively, the presence of high intermediate frequency alleles and positive Tajima’s D could be a signal of balancing selection.…”
Section: Discussionmentioning
confidence: 99%
“… Iannello et al (2021) investigate mitochondrial heteroplasmy in a bivalve species with doubly uniparental inheritance. Their results reveal pronounced differences in mitochondrial genotypes among different tissues, possibly as a result of a strong bottleneck early during development ( Iannello et al 2021) .…”
Section: A Special Section With New Insights Into Within-individual Genome Variationmentioning
confidence: 99%